Genetic divergence among genetic groups of Gir crossbreds - MOTE, MAHENDRA GORAKH; BHOITE, UDDHAV YASHWANTRAO; NIMBALKAR, CHARUDATTA ANANTRAO; MANDAKMALE, SANJAY DATTATRAYA (The Indian Journal of Animal Sciences, 2019)
Comparative evaluation of FG (50% HF + 50% Gir), IFG (Interse of FG), FJG (50% HF + 25% Jersey + 25% Gir), IFJG (Interse of FJG) and R (50% HF + 12.50% Jersey + 37.50% Gir) crosses of Gir was done on the basis of age at first conception (AFCon), lactation length (LL) and 300 days milk yield (300 DMY) of first, second and third lactations using Mahalanobis D2 statistics. The genetic group differences were significant for each trait separately and simultaneously (V-stat) in all the three lactations. The differences in the D2 values among genetic groups in all three subsets were significant except IFG with R genetic group in first lactation. The total D2 values for AFCon, LL and 300 DMY were 18.85, 1.29 and 8.53 in first; 19.65, 1.90 and 6.91 in second and 21.22, 1.32 and 6.83, in third lactation, respectively. The per cent contribution of AFCon to the total D2 value was maximum followed by 300 DMY and lowest of LL in first, second and third lactation, respectively. Based on D2 values, in first lactation, the FG and FJG (F1) genetic groups were placed in cluster 2 and IFG, IFJG and R genetic groups in cluster 1. In second and third lactations, IFG and IFJG genetic groups formed cluster 1, FG and FJG groups grouped in to cluster 2 and R genetic group formed cluster 3. The magnitude of inter-cluster distance was greater than intra-cluster distance.